Farmers Rate Fertilizer Subsidy Delivery Highly in Periurban Rice Areas: Petani Menilai Penyaluran Pupuk Bersubsidi Sangat Baik di Wilayah Sentra Padi Periurban - Firmansyah Ramadhani; Mirza Andrian Syah; Nuriah Yuliati (Indonesian Journal of Innovation Studies, 2026)
General Background: Subsidized fertilizer distribution plays an essential role in supporting rice production by ensuring that farmers obtain agricultural inputs through government assistance programs. Specific Background: In Indonesia, the distribution system is evaluated using the "7 Right" principles, namely the right type, quantity, price, place, time, quality, and target recipients, yet implementation challenges remain in several farming areas. Knowledge Gap: Limited evidence is available regarding farmers’ perceptions of subsidized fertilizer distribution performance in periurban rice production areas using the comprehensive "7 Right" framework. Aims: This study aimed to examine farmers’ perceptions of subsidized fertilizer distribution and determine the overall distribution performance in Cangkringsari Village, Sukodono District, Sidoarjo Regency. Results: A quantitative descriptive approach was conducted using questionnaires administered to 66 randomly selected rice farmers registered in the 2025 Definitive Plan for Group Needs (RDKK). The findings showed very high scores across all distribution dimensions, including the right type (4.45), quantity (4.38), price (4.29), place (4.42), time (4.60), quality (4.38), and target recipients (4.43). The overall distribution performance reached 88%, indicating a very high level of implementation according to farmers’ assessments, although several operational problems were still reported. Novelty: This study provides an integrated evaluation of subsidized fertilizer distribution in a periurban rice farming area using farmers’ assessments across all "7 Right" distribution indicators. Implications: The findings support the continued implementation of subsidized fertilizer programs while highlighting the importance of addressing remaining operational constraints to sustain farmer satisfaction and program performance. Highlights: Farmers assigned very high ratings to every distribution criterion within the seven-principle assessment framework. Overall program implementation achieved an 88% performance level based on respondents' evaluations. Operational issues remain despite consistently positive assessments of the distribution system. Keywords: Farmer Perception, Effectiveness, Distribution, Subsidized Fertilizer